Innovation and Improving Student Training Quality of Philology Teacher Education Program to Meet Requirements of the 2018 Philology Curriculum - Hien, Pham Thi Thu (VNU Journal of Science: Education Research; Vol 35 No 3DO - 10.25073/2588-1159/vnuer.4288, 2019)
The new Philology Curriculum was launched at the end of 2018. This curriculum has many new points, but the most significant is the requirement for teaching informational texts and teaching to develop literacy competency for students. Therefore, it is necessary to renovate and improve the quality of training students in Philology Teacher Education Program by updating the content of some current modules, introducing new modules to help students after upon graduation, meet the requirements of the 2018 Philology Curriculum.